Associations of impaired grip strength and gait function with the severity of erectile dysfunction in men undergoing dialysis: a cross-sectional study. (31st December 2022) - Fujita, Naoki; Hatakeyama, Shingo; Momota, Masaki; Tobisawa, Yuki; Yoneyama, Tohru; Okamoto, Teppei; Yamamoto, Hayato; Yoneyama, Takahiro; Hashimoto, Yasuhiro; Yoshikawa, Kazuaki; Ohyama, Chikara
Abstract: Objective: To investigate the associations of impaired muscle strength and gait function with the severity of erectile dysfunction (ED) in men undergoing dialysis. Methods: This cross-sectional study included 63 men undergoing dialysis. ED was assessed with the Sexual Health Inventory for Men (SHIM). Patients were divided into the mild/moderate (SHIM score ≥8) and severe ED groups (SHIM score ≤7). Correlations between variables were analyzed using Spearman's rank correlation coefficient. Multivariable logistic regression analyses were performed to evaluate the impact of impaired grip strength and gait function on the severity of ED. Results: The median age of the study participants was 62 years; all had ED, with 67% having severe ED. Spearman's rank correlation test demonstrated significant negative and positive correlations between gait function and SHIM score ( ρ = −0.257, p  = 0.042) and between grip strength and SHIM score ( ρ  = 0.305, p  = 0.015), respectively. In the multivariable analyses, impaired grip strength was significantly associated with severe ED (odds ratio [OR]: 4.965, p  = 0.017), whereas gait function was not (OR: 3.147, p  = 0.064). Conclusion: Impaired muscle strength was significantly associated with severe ED, whereas impaired gait function had a marginal effect on this erectile condition.